Impacts of land use on soil carbon, nitrogen, and phosphorus in the Eastern Qilian Mountains - Shizhen Xu; Chunli Wang; Junju Zhou; Haihua Shan; Bingxing Li; Wei Shi; Dongxia Zhang; Guofeng Zhu; Xuemei Yang; Wei Wei; Haiyan Ma (PLoS ONE, 2025)
The dynamics and balance of soil carbon, nitrogen, and phosphorus significantly affect soil microbial activity and plants’ nutrient absorption and utilization. Understanding how different land-use types and climate fluctuations influence soil carbon, nitrogen, and phosphorus forms the basis for regional land-use optimization, scientific management, and enhancement of ecosystem service functions.This paper continuously collected soil samples from forestland, grassland, and cropland in the Binggou River Basin on the northern slope of the eastern section of the Qilian Mountains during 2018–2019. It analyzed variation patterns of soil carbon, nitrogen, and phosphorus across different land-use types in the study area and explored the impacts of land-use types and seasonal climate fluctuations on these soil elements, aiming to provide a scientific basis for soil management. Results showed that during 2018–2019, the average organic carbon content in forestland soil (48.82 g/kg) was higher than that in grassland (38.32 g/kg) and cropland (30.80 g/kg). Forestland soil had slightly higher average total nitrogen (TN) content than cropland, with grassland showing the lowest. Soil organic carbon (SOC) and TN contents in forestland and grassland were lowest in summer, while grassland’s total nitrogen content peaked in summer. The average total phosphorus (TP) content in cropland soil was slightly higher than in forestland and significantly higher than in grassland. The weaker carbon-sequestration capacity of cropland soil resulted in notably lower C:N (10.13) and C:P (47.38) ratios compared to forestland and grassland. Soil C:P and N:P ratios in grassland and cropland showed relatively small seasonal fluctuations, whereas those in forestland fluctuated more drastically, reaching the highest values in autumn. Excessively high C:P reduced soil phosphorus effectiveness. Regarding the soil vertical profile, SOC and TN contents in forestland and grassland both decreased with increasing soil depth, while the three nutrients in cropland soil exhibited more complex vertical variation characteristics. Overall, converting forestland and grassland to cropland significantly reduced soil carbon-sequestration capacity, shifting them from “carbon sinks” to “carbon sources” and increasing carbon emission risks. Changes in organic matter input, tillage practices, and chemical fertilizer use altered the vertical nutrient variation patterns in cropland soil.